Comparative pharmacokinetics of a fixed-dose combination vs concomitant administration of telmisartan and S-amlodipine in healthy adult volunteers - Oh M; Park SE; Ghim JL; Choi YK; Shim EJ; Shin JG; Kim EY (Dove Medical Press, 2017)
Minkyung Oh,1,2,* Sung-Eun Park,3,* Jong-Lyul Ghim,1–3 Young-Kyung Choi,1 Eon-Jeong Shim,1–3 Jae-Gook Shin,1–3 Eun-Young Kim1–3 1Department of Pharmacology, 2PharmacoGenomics Research Center, Inje University College of Medicine, Busan, 3Department of Clinical Pharmacology, Inje University Busan Paik Hospital, Busan, Republic of Korea *These authors contributed equally to this work Objective: This study compared the pharmacokinetic (PK) and safety profiles of a fixed-dose combination (FDC) formulation of telmisartan and S-amlodipine with those of concomitant administration of the two drugs.Materials and methods: This was an open-label, randomized, crossover study in healthy male Koreans. All subjects were administered an FDC tablet containing 40 mg telmisartan and 5 mg S-amlodipine and were also coadministered the same dose of both drugs given separately. The crossover study design included a 14-day washout period between the two treatments. Blood samples were collected up to 168 h following drug administration. The plasma concentrations of telmisartan and S-amlodipine were determined by liquid chromatography tandem mass spectrometry. PK parameters and plasma concentration–time curves were compared. Safety was assessed by measuring vital signs, clinical laboratory tests, physical examinations, and patient interviews.Results: The geometric mean ratios and 90% CIs for the maximum plasma concentration (Cmax) and area under the curve from time zero to the last sampling time (AUCt) were 0.8782 (0.8167–0.9444) and 0.9662 (0.9210–1.0136) for telmisartan and 1.0069 (0.9723–1.0427) and 1.0324 (0.9969–1.0690) for S-amlodipine, respectively. A total of 36 adverse events (AEs) were reported by 23 subjects, but no statistical differences were observed between the two treatments. The most frequently reported AE was a mild-to-moderate headache that was generally self-limiting.Conclusion: For both telmisartan and S-amlodipine, the Cmax and AUCt 90% CIs were between ln (0.8) and ln (1.25). These results suggest that the FDC formulation is pharmacokinetically bioequivalent and has a similar safety profile to the coadministration of these drugs. Keywords: bioequivalence, fixed-dose combination, pharmacokinetics, S-amlodipine, telmisartan